2016
DOI: 10.1177/0956797616636631
|View full text |Cite
|
Sign up to set email alerts
|

Going All In

Abstract: When faced with risky decisions, people typically choose to diversify their choices by allocating resources across a variety of options and thus avoid putting "all their eggs in one basket." The current research revealed that this tendency is reversed when people face an important cue to mating-related risk: skew in the operational sex ratio, or the ratio of men to women in the local environment. Counter to the typical strategy of choice diversification, findings from four studies demonstrated that the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 39 publications
(52 reference statements)
0
17
0
Order By: Relevance
“…This is despite the fact that key risk factors for adolescent school injuriesaggression and risk-takinghave consistently shown to be highly susceptible to contextual influences. Moreover, a growing body of literature suggests that male-skewed sex ratios increase adolescent risk-taking and in particular physical aggression (34,36,40,53,54,(57)(58)(59)61,(71)(72)(73)76,77). In this paper, we bring together these spheres of expertise to explore the role of classroom sex compositions as a contextual risk factor for adolescent school injuries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is despite the fact that key risk factors for adolescent school injuriesaggression and risk-takinghave consistently shown to be highly susceptible to contextual influences. Moreover, a growing body of literature suggests that male-skewed sex ratios increase adolescent risk-taking and in particular physical aggression (34,36,40,53,54,(57)(58)(59)61,(71)(72)(73)76,77). In this paper, we bring together these spheres of expertise to explore the role of classroom sex compositions as a contextual risk factor for adolescent school injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for sex ratio effects on risk-taking also exists. For instance, male-dominated contexts appear to instigate risk-taking in experimental (54,55,77) and health-risky behavior in non-experimental studies (59,78,79). Similarly, a study of risk-related mortality in Northern Ireland suggests that women might behave more risk-prone in male-skewed sex ratio environments (80).…”
Section: Introductionmentioning
confidence: 99%
“…An imbalanced sex ratio within a population influences behaviors related to both mating strategies and resource acquisition. For example, sex ratios have been linked to divorce rates (South, Trent, & Shen, 2001), marriage rates (Trent & South, 1989), risk-taking behaviors in investment (Ackerman, Maner, & Carpenter, 2016), economic decisions (Griskevicius et al, 2012), frequency of sexually transmitted infections (South & Trent, 2010), teenage pregnancy rates (Barber, 2001), national violent crime rates (Barber, 2000), and violence against women across the United States (Avakame, 1999) and across other nations (South & Messner, 1987). Most of these observed relationships between sex ratios and mating strategies have been considered using a broad theoretical approach grounded in evolutionary theory.…”
Section: The Influence Of Imbalanced Sex Ratio On Mating Behaviormentioning
confidence: 99%
“…A higher OSR predicts both women's and men's risk-taking and mating behaviors. In women, a higher OSR is associated with increased odds of marrying a high status man (Lichter et al, 1995), decreased tendency to choose a high-risk/highreturn financial investment option (Ackerman et al, 2016), and decreased sexual receptivity, as demonstrated by trends of decreased teenage pregnancies (Barber, 2000) and the tendency of women to wear less revealing clothing (Barber, 1999) within those populations. Meta-analyses (Janicke & Morrow, 2018;Weir et al, 2011) found that a higher OSR was associated with increased male intrasexual competition and aggression (cf.…”
Section: The Influence Of Imbalanced Sex Ratio On Mating Behaviormentioning
confidence: 99%
See 1 more Smart Citation